Business Incubation for Inclusive Economy: Implementation of Empower Academy Program in Empowering Disabled MSMEs in Malang City - iswanto, denny (PANGRIPTA, 2025)
Empowering people with disabilities through inclusive entrepreneurship is a strategic issue in building an equitable and competitive society. This research was conducted to analyze the role of young sociopreneurs in supporting inclusive entrepreneurship through collaborative business incubation programs in Malang City. The role of young sociopreneurs is considered crucial in overcoming socio-economic challenges faced by people with disabilities, particularly in accessing economic opportunities and achieving social integration. Unlike previous studies that mainly focused on general empowerment models or government-led initiatives, this research highlights the innovative contribution of young sociopreneurs as active facilitators in bridging resources, skills training, and business assistance. By employing a qualitative approach with in-depth interviews, observations, and documentation, this study involved sociopreneurs, government representatives, and beneficiaries with disabilities. The findings show that multi-stakeholder collaboration is the key to the success of business incubation programs. Young sociopreneurs not only foster economic independence but also enhance public awareness of the importance of social inclusion. This study contributes new insights by demonstrating how youth-driven sociopreneurship can be institutionalized into local development policies and ecosystem building. The results emphasize the potential of sustainable empowerment models that integrate social and economic inclusion of people with disabilities effectively into community-based development.